2018
DOI: 10.31254/phyto.2018.7212
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effect of aqueous bark extract of Oroxylum indicum L. on Vigna radiata L. (Green gram) seedlings

Abstract: The present investigation was carried out to evaluate the antiproliferative activity of aqueous bark extract of Oroxylum indicum L. on Vigna radiata L. (Green gram) seedlings. For different concentrations of plant extract (250, 500, 1000 and 2500 µg/mL) were treated in a 24 well microplate containing the Vigna radiata L. seeds (n=30) for 24, 48 and 72 hours. Colchicine (50 µg/mL) was used as standard drug. Seed germination and seedlings growth were measured. Mitotic index was calculated for the proliferation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The plant's seed and root include tetuin and 6-glucosides of baicalein, as well as oroxindin (Harminder et al 2011, Jagetia 2021, Lodh and Swamy 2020, Nair et al 1979). The plant's stem bark extract contains alkaloids, flavonoids, phenolic chemicals, saponins, and carbohydrates (Chetry and Bharali 2018, Pathak et al 2020, Samatha et al 2012.…”
Section: Plant Profile and Usesmentioning
confidence: 99%
“…The plant's seed and root include tetuin and 6-glucosides of baicalein, as well as oroxindin (Harminder et al 2011, Jagetia 2021, Lodh and Swamy 2020, Nair et al 1979). The plant's stem bark extract contains alkaloids, flavonoids, phenolic chemicals, saponins, and carbohydrates (Chetry and Bharali 2018, Pathak et al 2020, Samatha et al 2012.…”
Section: Plant Profile and Usesmentioning
confidence: 99%
“…O. indicum and its favonoid constituents have been reported to possess a wide range of biological and pharmacological activities [8,[10][11][12][13][14][15]. Over recent years, O. indicum has attracted a growing interest in treating various cancer cells, focusing on inhibiting cell division and proliferation [6,[16][17][18][19][20]. Talari et al have demonstrated the antiangiogenic efect of O. indicum on VEGF-induced neovascularization in the CAM model [21].…”
Section: Introductionmentioning
confidence: 99%